Promotional Sentences Used by Bali Tourism Office and the Philippines Departement of Tourism: A Systemic Functional Linguistics Study - Dewa Ayu Kadek Claria; I Gusti Ayu Agung Dian Susanthi; Ni Made Suwendri (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
The achievement of the Philippines in developing different destinations is an urgent concern for the advancement of tourism in Bali. Previous research showed that there was a shift in tourist interest from visiting beeches in Bali to the Philippines, raising high concerns about changes in global travel trends. The success is reflected from the selection of words by the Philippines to promote the beauty of its beaches through Instagram account. The effectiveness of using promotional sentences is also considered as an essential part of branding applied to the Instagram account of Bali Tourism Office. Therefore, this research aims to compare the effectiveness of promotional sentences on Instagram used by Bali and the Philippines Department of Tourism through Systemic Functional Linguistics (SFL) method. The results showed that Bali tourism office only had 3 posts related to beach element as a promotion. The Philippines Department of Tourism massively promoted the beaches in the past year with 37 posts in a year. A total of six processes in transitivity can be used to make promotional content more interesting. However, only material, mental, relational, behavioral, and existential processes were used in Instagram posts of the Philippines Department of Tourism’s Instagram account. These processes shaped the presentation of product by promotional messages, as well as the benefit and the included consumer.